Modelling of Berry phase and Fermi-level topologies for emergent quantum phenomena prediction in selected solid state systems - Tematio, Gaël-Pacôme Nguimeya (Department of Physics, 2026)
Topological materials host electronic states that remain robust against perturbations and offer routes to novel quantum functions. This thesis investigates three representative compounds - SrSi2, CoSi, and NbP - to reveal how external stimuli, namely tensile strain and electric fields, tune their electronic bands and topological traits. By combining first-principles calculations with model Hamiltonian experiments, we aim to uncover mechanisms behind quantum phase transitions (QPTs) and to establish design principles for materials with tailored quantum states. We perform density functional theory (DFT) calculations within the plane-wave pseudopotential framework using the Quantum ESPRESSO (QE) suite. Spin-orbit coupling (SOC) is included to capture relativistic effects critical for topological properties. We generate maximally localized Wannier functions (MLWFs) with Wannier90 and construct tight-binding (TB) models to compute Berry curvature, surface state spectra, and Fermi arc patterns via WannierTools. To probe QPTs in SrSi2, we employ the Quantum Lattice environment to simulate a renormalized graphene lattice, mapping analogies between external perturbations and topological responses in both systems.